Analisis Manajemen Risiko PT. Jaminan Pembiayaan Askrindo Syariah - Nurul Khasanah; Yusrizal Yusrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
ABSTRACTThis study aims to finds out how the risk management process is at PT Askindo syariah Financing Guarantee. This research uses a qualitative approach with a descriptive research type. The data used in this research are secondary data, namely data obtained from the results of publications that have been carried out by the company. The results of this study indicate that the company PT Guarantee Financing askrindo Syariah adopts PJOK No. 17/PJOK.03/2014 concerning the implementation of integrated risk management for financial conglomerates and PJOK No. 44/PJOK.05/2020 dated 2 September 2020 regarding the assessment of the risk level non-bank financial services institutions. The risk categories based on the PJOK above are divided into ten sections, namely : strategic risk, operational risk, guarantee risk, credit risk, market risk, liquidity risk, legal risk, compliance risk, reputation risk and intra-group risk.Keywords : Risk, Risk Management